An Algorithm of (n, t)-Threshold Proxy Signature with an Arbitrator - E. A. Tolyupa (Моделирование и анализ информационных систем)
The paper presents an (n, t)-threshold proxy signature scheme with an Arbitrator which enables an original signer to delegate the signature authority to sign a message on behalf of the original signer to proxy group P of n members. The original signer distributes the proxy key among the proxy group members in such a way that not less then t proxy signers and the Arbitrator can cooperatively sign messages on behalf of the original signer. Thus, for signing the document it is necessary to have agreements of not less then t members. The Arbitrator is a trusted third party. It receives the information from the t members and completes the calculation of the digital signature. A verifier can identify the original signer and the members of the proxy group P. The main feature is that n members of the proxy group can not calculate the proxy key and the original signer’s secret key.